Fröken Julie = Miss Julie [videorecording (DVD)] - Wirén, Dag, 1905-1986 (50 years of Janus Films, 2006)
Late 19th century. The young miss Julie lives in a mansion with her father. She has recently broken up her engagement but is attracted to one of the servants, Jean. They spend the midsummer night together, telling memories and their dreams to each other. Realizing that an affair between a man of the people and an aristocrat is impossible, they plan to escape to Switzerland.